Analysis and Optimization of SUV Drive Axle Abnormal Sound - Lü Chenming; Wang Tie; Zhang Ruiliang; Wang Daoyong (Jixie chuandong)
Aiming at the abnormal sound issue of the non-load SUV rear axle when driving in 90 100 km/h speed,by using the noise transfer function,the theoretical analysis is carried out,combining with NVH and vibration noise hammer test,the noise and vibration identification is carried out. Then,by using finite element method,the vibration response of the vehicle under different frequencies is analyzed,the fourth the frame supports is the key point while transfer vibration is identified,the cavity modes and noise amplification is caused.The experimental results are consistent with the results of finite element simulation. A solution is implemented to optimize the fourth frame support and restrain the transformation of the vibration noise. The test result shows the effect of interior noise reduction is significant,a reference for later project development is provided.